The rnc Gene Promotes Exopolysaccharide Synthesis and Represses the vicRKX Gene Expressions via MicroRNA-Size Small RNAs in Streptococcus mutans - Mao, Meng-Ying; Yang, Ying-Ming; Li, Ke-Zeng; Lei, Lei; Li, Meng; Yang, Yan; Tao, Xiang; Yin, Jia-Xin; Zhang, Ru; Ma, Xin-Rong; Hu, Tao (Frontiers in Microbiology, 2016)
Dental caries is a biofilm-dependent disease that largely relies on the ability of Streptococcus mutans to synthesize exopolysaccharides. Although the rnc gene is suggested to be involved in virulence mechanisms in many other bacteria, the information regarding it in S. mutans is very limited. Here, we demonstrated that deletion or overexpression of rnc in S. mutans significantly positively regulated exopolysaccharide synthesis and further altered biofilm formation. Meanwhile, the cariogenecity of S. mutans was decreased by deletion of rnc in a specific pathogen-free (SPF) rat model. Interestingly, analyzing the expression at mRNA level, we found the downstream vic locus was repressed by rnc in S. mutans. We used deep sequencing and bioinformatics analysis to predict, for the first time, three putative microRNA-size small RNAs (msRNAs) targeting vicRKX in S. mutans. The expression levels of these msRNAs were negatively correlated with vicRKX but positively correlated with rnc, indicating rnc probably repressed vicRKX expression through msRNAs at the post-transcriptional level. In all, the results present that rnc has a potential role in the regulation of exopolysaccharide synthesis and can affect vicRKX expressions via post-transcriptional repression in S. mutans. This study provides an alternative avenue for further research aimed at preventing caries.